ANALISIS PERAN BUDAYA SEKOLAH DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA KELAS V DI MIS NWDI 02 KELAYU TAHUN AJARAN 2023/2024 - Khairil Lina Susanti; Muchamad Tryianto; Sri Setyawati Mulianingsih (STKIP Subang, 2024)
This research is a qualitative research with descriptive method, data collectiontechniques used are observation, interviews and documentation. The informants inthis study consisted of two teachers, namely the head of the madrasah, a class Vteacher and class V students of MIS NWDI 02 Kelayu. The subject of this study ishow the role of school culture in the formation of religious character of class Vstudents. The population in the class is 33 students. The results of the study showthat the religious character of students is formed through several types of schoolculture, namely praying Duha' and Zuhur in congregation, reading the Yasin surah,memorization, selecting young preachers (pildacil), one day one surah (one day onesurah), listening to lectures, and carrying out the Commemoration of IslamicHolidays (PHBI) which has been determined by the school. So it is concluded thatschool culture has an important role and a big impact on the formation of religiouscharacter of class V students of MIS NWDI 02 Kelayu. The research results showthat there are 5 students out of 33 students who still often arrive late whenparticipating in the school's IMTAQ cultural activities, wear incomplete clothing, andplay during IMTAQ activities so that special guidance is needed from teachers, bothclass teachers and Islamic religious education teachers in handling them.